Physical therapy in the conservative treatment for anterior cruciate ligament rupture followed by contralateral rupture: case report - Gabriel Peixoto Leão Almeida; Gilvan de Oliveira Arruda; Amélia Pasqual Marques (Universidade de São Paulo, 2014)
Although the surgical reconstruction be the obvious indication for the anterior cruciate ligament (ACL) lesion, there is no consensus on whether the results of surgery are superior to those obtained with nonsurgical management. The objective of this report was to describe a case of nonsurgical treatment for ACL rupture followed by a contralateral rupture. A 28-year-old female practitioner of muay-thai and handball suffered a non-contact ACL rupture in the left knee, and three months after the end of rehabilitation, the patient suffered a second non-contact ACL rupture in the contralateral knee and also received nonsurgical treatment. After both ruptures the patient received a treatment program focused on the strengthening of the quadriceps and hamstring muscles, trunk stabilization, plyometrics exercises, perturbation training, and return-to-sport training. After the treatments the patient exhibited absence of pain; normal muscular function and knee extension and flexion strength; normal range of motion; normal hop tests (<10% difference between members); improvement in the knee functional capacity and total return to normal activities. After two years of follow-up, the patient remained pain free and with normal knee function. The findings demonstrate the physical therapy effects in the nonsurgical treatment of bilateral ACL rupture. The patient could return to sport practice without instability. Further studies with a larger sample are needed to assess the recovery capacity and the full return to sport activities of patients with ACL injury.